2000
DOI: 10.1097/00002030-200007070-00010
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, dose-finding study with didanosine plus stavudine versus didanosine alone in antiviral-naive, HIV-infected Thai patients

Abstract: The d4T/ddI combination was superior to ddI alone in producing HIV-1 viral suppression. At week 48, > 60% of patients treated with this combination reached HIV-1 RNA levels < 500 copies/ml. Receiving high dose ddI but not d4T may correlate with a better viral suppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…52 53 55 – 62 66 77 79 80 Double therapy resulted in significantly better clinical outcomes than monotherapy did (fig 6) (odds ratio for disease progression/death was 0.6, 0.5 to 0.7). There was some heterogeneity, but this seemed to be largely accounted for by one large trial of protease inhibitors 79.…”
Section: Resultsmentioning
confidence: 99%
“…52 53 55 – 62 66 77 79 80 Double therapy resulted in significantly better clinical outcomes than monotherapy did (fig 6) (odds ratio for disease progression/death was 0.6, 0.5 to 0.7). There was some heterogeneity, but this seemed to be largely accounted for by one large trial of protease inhibitors 79.…”
Section: Resultsmentioning
confidence: 99%
“…Although the data on a lower dose of stavudine are scarce, there is evidence that patients can maintain virologic suppression, improve immunologic response and decrease stavudine-related adverse events while on ART [34–37]. One study reported that a switch to a half dose of stavudine (15 or 20 mg) modestly improved mitochondrial function and lessened the loss of bone mineral density [35].…”
Section: Discussionmentioning
confidence: 99%
“…Dose reduction of d4T to 20 mg twice daily for patients with body weight less than 60 kg and 30 mg twice daily for patients with body weight more than 60 kg has been shown to be effective, with a more favorable toxicity profile [22,33]. Furthermore, AZT 300 mg twice daily, which is the recommended dosage, results in a 5-fold increases in plasma AZT concentrations in Thais [34].…”
Section: Introductionmentioning
confidence: 99%